ANALYSIS OF DOMINANT FACTORS INFLUENCING MEDICAL WASTE GENERATION FROM HEALTH CARE FACILITIES IN INDONESIA AND MULTICRITERIA ANALYSIS FOR ITS HANDLING (STUDY CASE IN THE CITY OF SURABAYA) - Alfirdaus, Zahrah
Waste generated from healthcare facilities such as clinics, public health centers (puskesmas) and hospitals, consists of medical waste and non medical waste, require specific management consist of separation, collection, storage, transport, and treatment. The rate of generation as well as the composition of the waste must be determined as the basis of a good management. This research objectives were to evaluate the existing medical solid waste management in the healthcare facilities in Surabaya, to determine the dominant factors that affect the medical waste generation, to calculate the mass balance of the generated medical waste, as well as to identify stakeholders in order to establish alternatives of optimum medical solid waste management considering various aspects. This research was performed by direct observation and structured interview using questionnaires based on technical regulation from the applicable laws in Indonesia, at sampled locations, i.e., 17 clinics, 16 public health centers, and 12 hospitals. A direct measurement by weighing the waste during sampling time also performed to determine the waste generation as well as data collection regarding the factors affecting it. Statistical analysis used were homogeneity test, correlation, multiple linearity regression, stepwise regression and principal component regression. The establishment of alternatives of scenarios was completed by literature study and evaluation on existing medical waste management. The determination of the criteria and sub criteria was supported by previous studies and inputs from the stakeholders. Evaluation of the criteria and sub criteria was accomplished using the multicriteria analysis to formulate the alternative of scenario as well as to determine the chosen one. Healthcare facilities in Surabaya consist of clinics, public health centers, and hospitals that generate medical and non-medical solid waste which management consists of separation, collection, storage, transport, and treatment. The medical waste management have not completely safe and perform in accordance with the regulations with the level of compliance for clinics was 15,4%, public health center was 43,9% and hospital was 57,6%. The solid waste separation in public health centers consist of medical waste with the category as infectious, sharps and non medical waste with the generation rate of 0,017 kg/patient/day, 0,006 kg/patient/day, and 0,030 kg/patient/day, respectively. The solid waste composition was 34%, 13% and 53% for outpatients and 31%, 9% and 60% for inpatient public health center. Medical waste in clinics was separated into categories such infectious, sharps and non medical waste, with the generation rate of 0,040 kg/patient/day, 0,023 kg/patient/day, and 0,039 kg/patient/day, respectively. The composition of clinics solid waste for infectious, sharps and non medical waste were 46%, 21% and 33% for pratama clinics, and 37%, 24% and 39% for utama clinics, respectively. The hospitals can be categorized based on class, ownership, type of service, economic level of the patients, and the number of medical waste separation, which show different solid waste generation. Solid waste generation rate for class A hospital is 1,131 kg/bed/day, class B 0,777 kg/bed/day, class C 0,454 kg/bed/day, and class D 0,179 kg/bed/day. The medical waste generation of general hospitals and specialist hospitals were 0,832 kg/bed/day, and 0,234 kg/bed/day, respectively. Government hospital waste generation was 0,896 kg/bed/day, while the private one was 0,568 kg/bed/day. The hospitals which provide services for patients with high economic level has medical waste generation of 0,390 kg/bed/day, while for lower income patients was 0,801 kg/bed/day. As for hospitals with only two types of waste separation generate as much as 0,564 kg/bed/day and with three types of waste or more separation generate 0,901 kg/bed/day of medical waste. Hospitals provide services in clinics for outpatient generated medical waste as much as 0,037 kg/patient/day and 0,039 kg/patient/day for non medical waste. The category for hospitals medical waste consisted of infectious, sharps, cytotoxic, farnaceutical, and packaging with the composition 91,86%, 6,36%, 0,11%, 0,11% and 1,56%, respectively. The medical waste generated in clinics followed equation: Y=0,131+0,039X2+0,150X6-0,121X5, which affected by the average of outpatients’ numbers (X2), the number of other staff (X6), and the number of paramedics (X5). As for clinic’s non-medical waste, the dominant factor was the average number of outpatients (X2), following the equation: Y=0,1367+0,0240X2. The dominant factors for medical waste generation in public health center was the average number of outpatients (X2), the average number of inpatients (X1), and the number of doctors, with the equation Y=-0,0345+0,0143X2+0,50X1+0,181X5, while for non-medical waste affected by the average number of inpatients (X1) and was the average number of outpatients (X2) with equation: Y=1,114+1,50X1+0,0175X2. Identification of the factors affecting solid waste generation in hospitals consisted of 17 variables. Correlation test was then performed resulted in 12 affecting variables, i.e., number of bed, total of patient, number of inpatient, number of outpatient, bed occupancy, the hospital class, land area, building area, number of doctor, number of paramedic, number of staff, and number of sanitarian. Hospital’s medical waste generation was affected by several dominant factors, i.e., seven variables consist of total number of patients, number of inpatients, bed occupancy, land area, building area, number of doctors, and number of sanitarians. The equation for waste generation function was Y = 2,45 + 1,49 X2+ 1,5 X3 + 1,5 X6 + 1,41 X12 + 1,49 X13 + 1,48 X14 + 1,4 X17. The same factors affecting non-medical waste generation, with the equation: Y = 2,84 + 1,9X2 + 1,91X3 + 1,91X6 + 1,82 X12 + 1,9X13 + 1,89 X14 + 1,81X17. Mass balance for medical waste of Surabaya City shows that the waste generated was 5455 kgg/day, in which hospital generate 5298 kg/day. Unfortunately, only five hospitals has incinerator that treat 1613 kg/day of waste. The rest of 3631,9 kg/day waste, together with 37,7 kg/day medical waste from public health centers, and 35,1 kg/day from clinics was transported out of Surabaya by third party to be treated by licensed third party. As much as 84,3 kg/day of medical waste from the clinics the transport and treatment as unidentified. The medical waste management scenario consists of four alternatives, i.e., the existing condition, the optimization of hospitals’ incinerators, implementation of city scale temporary storage, and the development of city scale medical waste treatment. The evaluation of criteria and sub-criteria was performed using AHP, resulting in the priority difference of the aspects from different stakeholders. The hospital and clinic main priority was financial aspect, city government was organizational aspect, and academics was environmental aspect. The selection of scenarios using TOPSIS method results in Scenario D (centralized city scale treatment) as the best option, with the relatively different approach value for each stakeholder.